The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1063/1.110142
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the low doping efficiency of nitrogen acceptors in ZnSe grown by metalorganic chemical vapor deposition

Abstract: The origin of nitrogen acceptor compensation in ZnSe:N has been studied by secondary ion mass spectrometry (SIMS) and infrared absorption (FTIR) measurements. Nitrogen-doped ZnSe layers were grown by atmospheric pressure metalorganic chemical vapor deposition. Ammonia gas was used as a nitrogen source. SIMS analysis has revealed that hydrogen was incorporated only into the ZnSe:N layer with the same concentration as nitrogen. FTIR measurements at 11 K strongly suggest the presence of N—H bonding at 3193 cm−1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(27 citation statements)
references
References 9 publications
2
25
0
Order By: Relevance
“…IR spectroscopy showed that MOVPE-grown ZnSe contained N-H complexes. 58,59 Annealing in nitrogen gas (N 2 ) increased the PL emission intensity whereas annealing in H 2 did not; the activation mechanism was attributed to the release of H 2 from N-H bonds. 60 In ZnSe grown by gas source MBE, undoped regions contained background levels of hydrogen Fig.…”
Section: Hydrogen In Semiconductorsmentioning
confidence: 98%
“…IR spectroscopy showed that MOVPE-grown ZnSe contained N-H complexes. 58,59 Annealing in nitrogen gas (N 2 ) increased the PL emission intensity whereas annealing in H 2 did not; the activation mechanism was attributed to the release of H 2 from N-H bonds. 60 In ZnSe grown by gas source MBE, undoped regions contained background levels of hydrogen Fig.…”
Section: Hydrogen In Semiconductorsmentioning
confidence: 98%
“…These results have been obtained either in OMVPE grown samples in which hydrogen was non intentional [11,17,18,20,21] or in samples in which hydrogen had been intentionally introduced either during the MBE growth [16] or by exposition to a hydrogen or deuterium radio frequency plasma [19]. In the case of arsenic in ZnSe, deuterium had been also substituted to hydrogen as the carrier gas and in this case, the deuterium related mode has also been reported [21].…”
mentioning
confidence: 52%
“…The hydrogen passivation is one of the most important causes of the poor results of the p-type doping in MOVPE, 3 and the presence of N-H bonds in MOVPE-grown samples was confirmed experimentally. 10,11 On the other hand, the thermal treatment at relatively low temperatures leads to the extraction of the hydrogen from the samples, resulting in successful activation of the dopant. 3 Therefore the reconstruction of the excitonic spectra may be connected with the hydrogen removal from the samples.…”
Section: Photoluminescence Spectramentioning
confidence: 99%